Enhancing Communication in Adults with Dementia and Age-Related Hearing Loss - Mamo, Sara K.; Oh, Esther; Lin, Frank R. (Seminars in Hearing, 2017)
For many adults with dementia, age-related hearing loss is undiagnosed and/or untreated. Untreated hearing loss can exacerbate common dementia-related behavioral symptoms, such as depression, apathy, agitation. Despite the potential benefits to the individual and the family, pursuing and adopting hearing aids for persons with dementia presents with many challenges. As such, this group of vulnerable older adults is well suited for alternative approaches that adopt an interventional audiology framework. This article reviews alternative hearing care models that we have tested when working with older adults with cognitive impairments. We have found that some individuals show improvements in dementia-related problem behaviors and/or in measures of social engagement after brief aural rehabilitation interventions that provide non-custom amplification. We have developed simple training materials to help family and professional caregivers use communication strategies and non-custom amplification. Providing services that can be integrated into the person's broader dementia care has the potential to improve communication and quality of life for individuals and families. There are opportunities in this population to provide basic, simple strategies and make substantial improvements as long as we adopt approaches that bring the services to the people, instead of bringing the people to us in the audiology clinic.
Keywords: Dementia; communication strategies; over-the-counter amplification